A long-acting and quick-fogging moisture control material for vehicle-mounted cameras

CN116875205BActive Publication Date: 2026-10-30NINGBO BOOER NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310837579.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2026-10-30
Estimated Expiration
2043-07-10

AI Technical Summary

Technical Problem

[0006]但现有控湿材料在长期快速吸收湿气方面仍存在不足,为了解决上述技术问题,提供一种可用于车载摄像头的长效快速消雾控湿材料,对于汽车的安全驾驶意义重大

Benefits of technology

[0030]1、本发明的羧甲基纤维素钠聚合物提供更多亲水基团;微量纤维素钠可很好的起到粘结性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004329408760000111
    Figure BDA0004329408760000111
  • Figure HDA0004329408770000011
    Figure HDA0004329408770000011
Patent Text Reader

Abstract

The present application relates to the field of humidity control material, and specifically to a long-acting and fast-fogging humidity control material for vehicle-mounted camera; the sodium carboxymethyl cellulose polymer of the present application provides more hydrophilic groups; trace sodium cellulose can well play a bonding performance; the present application uses silica sol and saturated solution of lithium chloride / calcium chloride / magnesium chloride to prepare a composite adsorbent, and improves the moisture absorption performance by halogen salt solution; silica sol is used as adsorbent medium, which can be better adsorbed on the substrate, and can more effectively improve the moisture absorption efficiency; and the structural stability of silica sol is good, which can increase its long-term weather resistance; the present application uses glycerol and glycol as solvents, and polyols provide multiple hydroxyl groups to improve the hydrophilic performance and improve the moisture sensitivity; the long-acting and fast-fogging humidity control material for vehicle-mounted camera prepared by the present application has the advantages of short fogging time in 60 DEG C, 95% RH environment, fast moisture absorption, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of humidity control materials, and in particular to a long-lasting and rapid defogging humidity control material for vehicle cameras. Background Technology

[0002] As the eyes of intelligent vehicles, automotive cameras play a crucial role in autonomous driving. The core of the optical equipment is the optical automotive camera and its components. The latest automotive optical camera components utilize high-frequency motors and higher-resolution cameras while further reducing the component's size. This results in the camera generating twice the heat of traditional components during operation. The high heat generated inside the camera can cause fogging when the external environment experiences rapid cooling due to climate changes, rain, snow, or significant temperature fluctuations. Since PTZ cameras rely on optical imaging principles, severe fogging affects their transmittance, leading to blurry images or even completely white areas, directly impacting monitoring effectiveness and rendering them ineffective. Therefore, quickly absorbing moisture from the optical automotive camera is crucial for preventing fogging and ensuring safe driving.

[0003] Chinese Patent CN202210212955.8 discloses a phase change temperature and humidity control material, its preparation method, and its application. The phase change temperature and humidity control material of this invention is composed of the following components by mass percentage: shaped composite phase change material: 30%–70%; metal-organic framework material: 30%–70%. The preparation method of the phase change temperature and humidity control material of this invention includes the following steps: 1) mixing organic phase change material eutectic heated to a molten state with porous silica, then cooling and pulverizing to obtain a shaped composite phase change material; 2) mixing the shaped composite phase change material and the metal-organic framework material evenly to obtain the phase change temperature and humidity control material.

[0004] Chinese Patent CN202111609070.3 discloses a moisture-controlling material comprising the following raw materials in parts by weight: 4-6 parts allyl cyclodextrin, 3-5 parts octavinyl POSS, 8-10 parts 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 1-3 parts 2,4-diamino-6-diallylamino-1,3,5-triazine, 6-10 parts volcanic rock, 8-12 parts silica gel, 4-8 parts porous hollow graphite material, 15-25 parts amino-terminated water-soluble hyperbranched polyamide, 5-7 parts glycidyl ether, 0.6-1.2 parts initiator, and 80-100 parts solvent. The patent also discloses a method for preparing the moisture-controlling material.

[0005] Chinese Patent CN202010576742.4 discloses a bio-intelligent, biodegradable humidity-controlling material and its preparation method, made from the following raw materials in weight percentages: 5-30% acrylic chitosan graft, 0.1-30% cellulose, 1-35% inorganic salts, and the balance being water. This invention uses a biodegradable acrylic chitosan graft composite porous hydrogel formed by grafting acrylic functional groups onto chitosan as a carrier, then blends it with cellulose and inorganic salts to produce a humidity-controlling material with excellent humidity-regulating properties that is bio-intelligent, biodegradable, and recyclable. The main raw materials of this invention are derived from marine organisms, which are widely available, inexpensive, biodegradable, and highly recyclable. The resulting humidity-controlling material is non-toxic, harmless, and has good stability, making it an environmentally friendly humidity-controlling material suitable for large-scale production. Furthermore, the low synthesis temperature of this invention significantly reduces the production costs associated with complex equipment and high temperatures.

[0006] However, existing moisture-controlling materials still have shortcomings in terms of long-term and rapid moisture absorption. In order to solve the above technical problems, a long-lasting and rapid defogging and moisture-controlling material that can be used in vehicle cameras is of great significance for safe driving. Summary of the Invention

[0007] The purpose of this invention is to provide a long-lasting and fast defogging moisture control material for vehicle cameras, which belongs to the field of moisture control materials.

[0008] The technical solution adopted in this invention is:

[0009] A long-lasting and rapid defogging moisture-controlling material for vehicle-mounted cameras comprises, from top to bottom, a breathable membrane, a moisture-controlling sheet, and double-sided adhesive tape. The moisture-controlling sheet (1-3 layers) is stacked sequentially on the double-sided adhesive tape, and the breathable membrane is stacked on top of the moisture-controlling sheet. The bottommost moisture-controlling sheet is attached to the double-sided adhesive tape via transfer. The breathable membrane is then stacked on top of the topmost moisture-controlling sheet. The breathable membrane and double-sided adhesive tape are bonded together on all four sides using a pressing process, followed by laser edge cutting to obtain the long-lasting and rapid defogging moisture-controlling material for vehicle-mounted cameras. The thickness of the breathable membrane is 0.1-0.3 mm, the thickness of the single-layer moisture-controlling sheet is 0.4-1 mm, and the thickness of the double-sided adhesive tape is 0.5-0.8 mm.

[0010] Preferably, the method for preparing the humidity control sheet is as follows: S1: Weigh 3-10 parts of the polymer by weight and dissolve it in 30-50 parts of solvent, then add 25-35 parts of composite adsorbent, mix evenly, and obtain a humidity control solution;

[0011] S2: Immerse the substrate in the humidity control solution for 5-20 seconds, remove it, dry it, and then laser cut it into a humidity control sheet.

[0012] Preferably, the polymer is sodium carboxymethyl cellulose.

[0013] Preferably, the solvent is glycerol or glycol.

[0014] Preferably, the substrate is polyester fiber.

[0015] Preferably, the drying temperature of S2 is 100-120℃ and the drying time is 5-15 min.

[0016] Preferably, the preparation method of the composite adsorbent is as follows:

[0017] Weigh 45-65 parts by weight of saturated halide salt solution and mix it with 25-35 parts by weight of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0018] More preferably, the saturated halide salt solution is calcium chloride, lithium chloride, or magnesium chloride.

[0019] A further preferred embodiment is the preparation method of the organic rare earth metal framework silica sol as follows:

[0020] S1: Add 2-5 parts allyl β-cyclodextrin, 3-6 parts lanthanum chloride, and 100-200 parts ethanol to the stirred tank according to the mass fraction, and stir at 35-50℃ for 1-4 hours;

[0021] S2: According to the mass fraction, add 30-50 parts of mercapto-modified silica sol and 3-6 parts of ethylenediamine to a stirring vessel, stir at 55-70℃ for 30-60 min, then add 0.06-0.4 parts of lithium acrylate and stir for 100-150 min, then remove ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0022] A further preferred embodiment is the preparation method of the thiol-modified silica sol as follows:

[0023] By weight, at room temperature, 10-16 parts of mercaptosiloxane are added to 100-200 parts of ethanol in a reaction vessel, stirred, and the pH of the system is adjusted to 2-4 with dilute acetic acid. Stirring is continued for 1-3 hours. Then, 30-50 parts of silica sol are added dropwise and ultrasonically dispersed for 10-30 minutes. After the addition is complete, the reaction temperature is adjusted to 60-70℃, and the reaction is continued for 2-5 hours. The ethanol is removed by distillation, and 300-500 parts of silica sol are added and ultrasonically dispersed for 10-30 minutes to obtain mercapto-modified silica sol.

[0024] More preferably, the mercaptosiloxane includes γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane.

[0025] The reaction mechanism of the organic rare earth metal framework silica sol in this invention is as follows:

[0026] (1) Allyl β-cyclodextrin reacts with lanthanum chloride to form an allyl organolanthanum metal framework complex;

[0027] (2) The mercapto-modified silica sol undergoes a mercapto-olefin addition reaction with the allyl group in the allyl organolanthanum metal framework complex.

[0028] (3) The mercapto-modified silica sol undergoes a mercapto-olefin addition reaction with lithium acrylate to obtain an organic rare earth metal framework silica sol.

[0029] The present invention provides a long-lasting and rapid defogging moisture-controlling material for vehicle-mounted cameras. Compared with the prior art, the present invention has the following significant advantages:

[0030] 1. The sodium carboxymethyl cellulose polymer of the present invention provides more hydrophilic groups; trace amounts of sodium cellulose can effectively provide adhesive properties;

[0031] 2. This invention uses an organic rare-earth metal framework silica sol and a saturated solution of lithium chloride / calcium chloride / magnesium chloride to formulate a composite adsorbent. The hygroscopic performance is enhanced by the use of a halogen salt solution. Using the organic rare-earth metal framework silica sol as the adsorbent medium allows for better adsorption onto the substrate, effectively improving its hygroscopic efficiency. Furthermore, the organic rare-earth metal framework silica sol exhibits good structural stability, increasing its long-term weather resistance. Its porous structure and electro-attraction increase the contact area of ​​water molecules on the material surface, thereby improving the material's adsorption capacity for water molecules. Simultaneously, lithium enhances the adsorption capacity of the organolanthanum metal framework for water molecules.

[0032] 3. This invention uses glycerol and glycol as solvents, and polyols provide multiple hydroxyl groups to enhance their hydrophilicity and thus improve their moisture sensitivity.

[0033] 4. The moisture-controlling material for long-lasting and rapid defogging of vehicle cameras prepared by this invention has the advantages of short defogging time and rapid moisture absorption in an environment of 60℃ and 95%RH. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the product structure. Detailed Implementation

[0035] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.

[0036] Example 1

[0037] A moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras includes a breathable membrane, a single-layer moisture-controlling sheet, and double-sided adhesive tape. The breathable membrane is stacked on top of the moisture-controlling sheet, which is then attached to the double-sided adhesive tape via a transfer process. The breathable membrane and the double-sided adhesive tape are bonded together on all four sides using a pressing process, followed by laser edge cutting to obtain the moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras. The breathable membrane has a thickness of 0.2 mm, the single-layer moisture-controlling sheet has a thickness of 0.5 mm, and the double-sided adhesive tape has a thickness of 0.5 mm.

[0038] The method for preparing the humidity control sheet is as follows:

[0039] S1: Weigh 3g of polymer and dissolve it in 30g of solvent, then add 25g of composite adsorbent, mix well, and obtain a humidity-controlled solution;

[0040] S2: The substrate is immersed in a moisture-controlled solution for 5 seconds, then removed, dried, and laser-cut into a sheet of 40mm*40mm*0.5mm.

[0041] The polymer is sodium carboxymethyl cellulose.

[0042] The solvent is glycerol.

[0043] The substrate is polyester fiber.

[0044] The drying temperature of S2 is 100℃ and the drying time is 5 minutes.

[0045] The preparation method of the composite adsorbent is as follows:

[0046] Weigh 45g of saturated halide salt solution and mix it with 25g of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0047] The saturated halide salt solution is calcium chloride.

[0048] The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows:

[0049] S1: Add 2g allyl β-cyclodextrin, 3g lanthanum chloride, and 100g ethanol to a stirred tank and stir at 35°C for 1 hour;

[0050] S2: Add 30g of mercapto-modified silica sol and 3g of ethylenediamine to a stirred tank and stir at 55°C for 30min. Then add 0.06g of lithium acrylate and stir for 100min. Then remove the ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0051] The method for preparing the thiol-modified silica sol is as follows:

[0052] At room temperature, 10g of mercaptosiloxane was added to 100g of ethanol in a reaction vessel and stirred. The pH of the system was adjusted to 2 with dilute acetic acid and stirring was continued for 1 hour. Then, 30g of silica sol was added dropwise and ultrasonically dispersed for 10 minutes. After the addition was complete, the reaction temperature was adjusted to 60℃ and the reaction was stirred for 2 hours. The ethanol was removed by distillation, and 300g of silica sol was added and ultrasonically dispersed for 10 minutes to obtain mercapto-modified silica sol.

[0053] The mercaptosiloxanes mentioned include γ-mercaptopropyltriethoxysilane.

[0054] Example 2

[0055] This embodiment is basically the same as Embodiment 1, except that the preparation method of the humidity control sheet in this embodiment is as follows:

[0056] S1: Weigh 5g of polymer and dissolve it in 35g of solvent, then add 28g of composite adsorbent, mix well, and obtain a humidity-controlled solution;

[0057] S2: The substrate is immersed in a moisture-controlled solution for 10 seconds, then removed, dried, and laser-cut into a sheet of 40mm*40mm*0.5mm.

[0058] The polymer is sodium carboxymethyl cellulose.

[0059] The solvent is glycerol.

[0060] The substrate is polyester fiber.

[0061] The drying temperature of S2 is 105℃ and the drying time is 9 minutes.

[0062] The preparation method of the composite adsorbent is as follows:

[0063] Weigh 50g of saturated halide salt solution and mix it with 28g of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0064] The saturated halide salt solution is lithium chloride.

[0065] The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows:

[0066] S1: Add 3g allyl β-cyclodextrin, 4g lanthanum chloride, and 140g ethanol to a stirred tank and stir at 40°C for 2 hours;

[0067] S2: Add 35g of mercapto-modified silica sol and 4g of ethylenediamine to a stirred tank and stir at 60°C for 40min. Then add 0.2g of lithium acrylate and stir for 110min. Then remove the ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0068] The method for preparing the thiol-modified silica sol is as follows:

[0069] At room temperature, 12g of mercaptosiloxane was added to 140g of ethanol in a reaction vessel and stirred. The pH of the system was adjusted to 3 with dilute acetic acid and stirred for 2 hours. Then, 35g of silica sol was added dropwise and ultrasonically dispersed for 15 minutes. After the addition was complete, the reaction temperature was adjusted to 65℃ and the reaction was stirred for 3 hours. The ethanol was removed by distillation, and 350g of silica sol was added and ultrasonically dispersed for 15 minutes to obtain mercapto-modified silica sol.

[0070] The mercaptosiloxanes mentioned include γ-mercaptopropyltriethoxysilane.

[0071] Example 3

[0072] This embodiment is basically the same as Embodiment 1, except that the preparation method of the humidity control sheet in this embodiment is as follows:

[0073] S1: Weigh 8g of polymer and dissolve it in 45g of solvent, then add 32g of composite adsorbent, mix well, and obtain a humidity-controlled solution;

[0074] S2: The substrate is immersed in a moisture-controlled solution for 15 seconds, then removed, dried, and laser-cut into a sheet of 40mm*40mm*0.5mm.

[0075] The polymer is sodium carboxymethyl cellulose.

[0076] The solvent is glycol.

[0077] The substrate is polyester fiber.

[0078] The drying temperature of S2 is 115℃ and the drying time is 13min.

[0079] The preparation method of the composite adsorbent is as follows:

[0080] Weigh 60g of saturated halide salt solution and mix it with 32g of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0081] The saturated halide salt solution is lithium chloride.

[0082] The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows:

[0083] S1: Add 4g allyl β-cyclodextrin, 5g lanthanum chloride, and 180g ethanol to a stirred tank and stir at 45°C for 3 hours;

[0084] S2: Add 45g of mercapto-modified silica sol and 5g of ethylenediamine to a stirred tank and stir at 65°C for 50min. Then add 0.3g of lithium acrylate and stir for 140min. Then remove the ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0085] The method for preparing the thiol-modified silica sol is as follows:

[0086] At room temperature, 14g of mercaptosiloxane was added to 180g of ethanol in a reaction vessel and stirred. The pH of the system was adjusted to 3 with dilute acetic acid and stirred for 2 hours. Then, 45g of silica sol was added dropwise and ultrasonically dispersed for 25 minutes. After the addition was complete, the reaction temperature was adjusted to 65℃ and the reaction was stirred for 4 hours. The ethanol was removed by distillation, and 450g of silica sol was added and ultrasonically dispersed for 25 minutes to obtain mercapto-modified silica sol.

[0087] The mercaptosiloxanes mentioned include γ-mercaptopropyltrimethoxysilane.

[0088] Example 4

[0089] This embodiment is basically the same as Embodiment 1, except that the preparation method of the humidity control sheet in this embodiment is as follows:

[0090] S1: Weigh 10g of polymer and dissolve it in 50g of solvent, then add 35g of composite adsorbent, mix well, and obtain a humidity-controlled solution.

[0091] S2: The substrate is immersed in a moisture-controlled solution for 20 seconds, then removed, dried, and laser-cut into a sheet of 40mm*40mm*0.5mm.

[0092] The polymer is sodium carboxymethyl cellulose.

[0093] The solvent is glycol.

[0094] The substrate is polyester fiber.

[0095] The drying temperature of S2 is 120℃ and the drying time is 15min.

[0096] The preparation method of the composite adsorbent is as follows:

[0097] Weigh 65g of saturated halide salt solution and mix it with 35g of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0098] The saturated halide salt solution is magnesium chloride.

[0099] The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows:

[0100] S1: Add 5g allyl β-cyclodextrin, 6g lanthanum chloride, and 200g ethanol to a stirred tank and stir at 50°C for 4 hours;

[0101] S2: Add 50g of mercapto-modified silica sol and 6g of ethylenediamine to a stirred tank and stir at 70°C for 60min. Then add 0.4g of lithium acrylate and stir for 150min. Then remove the ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0102] The method for preparing the thiol-modified silica sol is as follows:

[0103] At room temperature, 16g of mercaptosiloxane was added to 200g of ethanol in a reaction vessel and stirred. The pH of the system was adjusted to 4 with dilute acetic acid and stirred for 3 hours. Then, 50g of silica sol was added dropwise and ultrasonically dispersed for 30 minutes. After the addition was complete, the reaction temperature was adjusted to 70℃ and the reaction was stirred for 5 hours. The ethanol was removed by distillation, and 500g of silica sol was added and ultrasonically dispersed for 30 minutes to obtain mercapto-modified silica sol.

[0104] The mercaptosiloxanes mentioned include γ-mercaptopropyltrimethoxysilane.

[0105] Example 5

[0106] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the long-lasting and fast defogging moisture control material for vehicle cameras includes a breathable membrane, two layers of moisture control sheets, and double-sided tape. The breathable membrane is stacked on top of the first layer of moisture control sheets, and the second layer of moisture control sheets is attached to the double-sided tape by transfer. The first layer of moisture control sheets is stacked on top of the second layer of moisture control sheets. The breathable membrane and the double-sided tape are bonded together on all four sides by a pressing process, and then laser-cut to obtain the long-lasting and fast defogging moisture control material for vehicle cameras. The thickness of the breathable membrane is 0.1 mm, the thickness of the single-layer moisture control sheet is 0.4 mm, and the thickness of the double-sided tape is 0.7 mm.

[0107] Example 6

[0108] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the long-lasting and fast defogging moisture control material for vehicle cameras includes a breathable membrane, three layers of moisture control sheets, and double-sided tape. The breathable membrane is stacked on top of the top layer of moisture control sheets, and the bottom layer of moisture control sheets is attached to the double-sided tape by transfer. The three layers of moisture control sheets are stacked together in sequence, and the breathable membrane and double-sided tape are bonded together on all four sides by a pressing process, followed by laser cutting to obtain the long-lasting and fast defogging moisture control material for vehicle cameras. The thickness of the breathable membrane is 0.3 mm, the thickness of the single-layer moisture control sheet is 1 mm, and the thickness of the double-sided tape is 0.8 mm.

[0109] Comparative Example 1

[0110] This embodiment is basically the same as Embodiment 1, except that the preparation method of the humidity control sheet in this embodiment is as follows:

[0111] S1: Weigh 3g of polymer and dissolve it in 30g of solvent, then add 25g of composite adsorbent, mix well, and obtain a humidity-controlled solution;

[0112] S2: The substrate is immersed in a moisture-controlled solution for 5 seconds, then removed, dried, and laser-cut into a sheet of 40mm*40mm*0.5mm.

[0113] The polymer is sodium carboxymethyl cellulose.

[0114] The solvent is glycerol.

[0115] The substrate is polyester fiber.

[0116] The drying temperature of S2 is 100℃ and the drying time is 5 minutes.

[0117] The preparation method of the composite adsorbent is as follows:

[0118] Weigh 45g of saturated halide salt solution and mix it with 25g of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0119] The saturated halide salt solution is calcium chloride.

[0120] The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows:

[0121] S1: Add 3g of lanthanum chloride and 100g of ethanol to a stirred tank and stir at 35°C for 1 hour;

[0122] S2: Add 30g of mercapto-modified silica sol and 3g of ethylenediamine to a stirred tank and stir at 55°C for 30min. Then add 0.06g of lithium acrylate and stir for 100min. Then remove the ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0123] The method for preparing the thiol-modified silica sol is as follows:

[0124] At room temperature, 10g of mercaptosiloxane was added to 100g of ethanol in a reaction vessel and stirred. The pH of the system was adjusted to 2 with dilute acetic acid and stirred for 1 hour. Then, 30g of silica sol was added dropwise and ultrasonically dispersed for 10 minutes. After the addition was complete, the reaction temperature was adjusted to 60℃ and the reaction was stirred for 2 hours. The ethanol was removed by distillation, and 300g of silica sol was added and ultrasonically dispersed for 10 minutes to obtain mercapto-modified silica sol.

[0125] The mercaptosiloxanes mentioned include γ-mercaptopropyltriethoxysilane.

[0126] Comparative Example 2

[0127] This embodiment is basically the same as Embodiment 1, except that the preparation method of the humidity control sheet in this embodiment is as follows:

[0128] S1: Weigh 3g of polymer and dissolve it in 30g of solvent, then add 25g of composite adsorbent, mix well, and obtain a humidity-controlled solution;

[0129] S2: The substrate is immersed in a moisture-controlled solution for 5 seconds, then removed, dried, and laser-cut into a sheet of 40mm*40mm*0.5mm.

[0130] The polymer is sodium carboxymethyl cellulose.

[0131] The solvent is glycerol.

[0132] The substrate is polyester fiber.

[0133] The drying temperature of S2 is 100℃ and the drying time is 5 minutes.

[0134] The preparation method of the composite adsorbent is as follows:

[0135] Weigh 45g of saturated halide salt solution and mix it with 25g of organic rare earth metal framework silica sol to obtain a composite adsorbent.

[0136] The saturated halide salt solution is calcium chloride.

[0137] The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows:

[0138] S1: Add 2g allyl β-cyclodextrin, 3g lanthanum chloride, and 100g ethanol to a stirred tank and stir at 35°C for 1 hour;

[0139] S2: Add 30g of mercapto-modified silica sol and 3g of ethylenediamine to a stirred tank and stir at 55°C for 30min. Remove ethanol by distillation to obtain an organic rare earth metal framework silica sol.

[0140] The method for preparing the thiol-modified silica sol is as follows:

[0141] At room temperature, 10g of mercaptosiloxane was added to 100g of ethanol in a reaction vessel and stirred. The pH of the system was adjusted to 2 with dilute acetic acid and stirred for 1 hour. Then, 30g of silica sol was added dropwise and ultrasonically dispersed for 10 minutes. After the addition was complete, the reaction temperature was adjusted to 60℃ and the reaction was stirred for 2 hours. The ethanol was removed by distillation, and 300g of silica sol was added and ultrasonically dispersed for 10 minutes to obtain mercapto-modified silica sol.

[0142] The mercaptosiloxanes mentioned include γ-mercaptopropyltriethoxysilane.

[0143] Evaluation of the implementation examples;

[0144] The methods for conducting anti-fogging and moisture absorption tests on Examples 1-4 and Comparative Examples 1-2 are as follows:

[0145] 1. Defogging test

[0146] The vehicle-mounted camera equipped with long-lasting and fast-acting defogging and humidity-controlling material was placed in an environment of 60℃ and 95%RH for different durations. After removing the vehicle-mounted camera, the power was turned on for 15 minutes to allow the internal components of the camera to heat up. After turning off the power, ice was applied to the outside for 1 minute. The defogging time of the lens was recorded.

[0147] 2. Moisture Absorption Test

[0148] Place the temperature and humidity recorder into six 250ml sealed containers.

[0149] Test ambient temperature: 25.2℃

[0150] Test method:

[0151] Moisture was injected into the sealed containers using a humidifier for 1-2 seconds. After stabilizing for 5 minutes, the humidity in each sealed container was between 85% and 90%. The completely dried moisture-controlling materials obtained from Examples 1-4 and Comparative Examples 1-2 were then placed into the sealed containers and sealed. The relative humidity value inside the containers was recorded for 5 minutes.

[0152] Table 1 Results of Anti-fogging Test and Moisture Absorption Test

[0153]

[0154] Through the comparison of data from the above embodiments and comparative examples, it can be seen that the moisture-controlling material for long-lasting and rapid defogging of vehicle cameras prepared by the present invention has the advantages of short defogging time and strong rapid moisture absorption in an environment of 60℃ and 95%RH.

[0155] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention. The scope of protection claimed by the appended claims and their equivalents is defined.

Claims

1. A long-lasting and rapid defogging moisture-controlling material for vehicle-mounted cameras, comprising, from top to bottom, a breathable membrane, a moisture-controlling sheet, and double-sided adhesive tape; wherein the moisture-controlling sheet comprises 1-3 layers, stacked sequentially on the double-sided adhesive tape, and the breathable membrane is stacked on top of the moisture-controlling sheet, characterized in that, The bottom moisture-control sheet is attached to the double-sided tape by transfer. The breathable membrane is stacked on the top moisture-control sheet. The breathable membrane and the double-sided tape are bonded together on all four sides by a pressing process and then laser-cut to obtain a long-lasting and fast defogging moisture-control material for vehicle cameras. The thickness of the breathable membrane is 0.1-0.3mm, the thickness of the single-layer moisture-control sheet is 0.4-1mm, and the thickness of the double-sided tape is 0.5-0.8mm. The method for preparing the humidity control sheet is as follows: S1: Weigh 3-10 parts of the polymer by weight and dissolve it in 30-50 parts of the solvent, then add 25-35 parts of the composite adsorbent, mix well, and obtain a humidity-controlled solution. S2: Immerse the substrate in the moisture control solution for 5-20 seconds, remove it, dry it, and laser cut it into a moisture control sheet; The preparation method of the composite adsorbent is as follows: Weigh 45-65 parts by weight of saturated halide salt solution and mix it with 25-35 parts by weight of organic rare earth metal framework silica sol to obtain composite adsorbent. The preparation method of the aforementioned organic rare earth metal framework silica sol is as follows: A1: Add 2-5 parts allyl β-cyclodextrin, 3-6 parts lanthanum chloride, and 100-200 parts ethanol to a stirred tank according to the mass fraction, and stir at 35-50℃ for 1-4 hours; A2: According to the mass fraction, add 30-50 parts of mercapto-modified silica sol and 3-6 parts of ethylenediamine to a stirring vessel, stir at 55-70℃ for 30-60 min, then add 0.06-0.4 parts of lithium acrylate and stir for 100-150 min, then remove ethanol by distillation to obtain an organic rare earth metal framework silica sol. The method for preparing the thiol-modified silica sol is as follows: By weight, at room temperature, 10-16 parts of mercaptosiloxane are added to 100-200 parts of ethanol in a reaction vessel, stirred, and the pH of the system is adjusted to 2-4 with dilute acetic acid. Stirring is continued for 1-3 hours. Then, 30-50 parts of silica sol are added dropwise and ultrasonically dispersed for 10-30 minutes. After the addition is complete, the reaction temperature is adjusted to 60-70℃, and the reaction is continued for 2-5 hours. The ethanol is removed by distillation, and 300-500 parts of silica sol are added and ultrasonically dispersed for 10-30 minutes to obtain mercapto-modified silica sol.

2. The moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras according to claim 1, characterized in that: The polymer is sodium carboxymethyl cellulose.

3. The moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras according to claim 1, characterized in that: The solvent is glycerol or glycol, and the substrate is polyester fiber.

4. The moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras according to claim 2, characterized in that: The drying temperature of S2 is 100-120℃, and the drying time is 5-15 min.

5. The moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras according to claim 1, characterized in that: The saturated halide salt solution is calcium chloride, lithium chloride, or magnesium chloride.

6. The moisture-controlling material for long-lasting and rapid defogging of vehicle-mounted cameras according to claim 1, characterized in that: The mercaptosiloxanes mentioned include γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane.

Citation Information

Patent Citations

  • Biological intelligent degradable humidity control material and preparation method thereof

    CN111635608A

  • A kind of humidity control material and preparation method thereof

    CN114395078B

  • Phase-change temperature-regulating and humidity-controlling material as well as preparation method and application thereof

    CN114672283A

  • Click preparation and application of allyl cationic cyclodextrin chiral resolution material

    CN105435760A

  • Long-acting humidity control material for battery pack and preparation method of long-acting humidity control material

    CN115157810A